Evaluating instrument responsiveness in joint function: The HOOS JR, the KOOS JR, and the PROMIS PF CAT. Issue 4 (9th October 2017) - Hung, Man; Saltzman, Charles L.; Greene, Tom; Voss, Maren W.; Bounsanga, Jerry; Gu, Yushan; Anderson, Mike B.; Peters, Christopher L.; Gililland, Jeremy; Pelt, Christopher E.
ABSTRACT: 12345Responsiveness is the ability to detect change over time and is an important aspect of measures used to detect treatment effects. The purpose of this study was to assess the responsiveness of the HOOS JR, the KOOS JR, and the PROMIS Physical Function (PF) computerized adaptive test (CAT) in a joint reconstruction practice. 983 patients were evaluated for joint conditions between 2014 and 2017 in an orthopaedic clinic and completed the three instruments at baseline and 3 and/or 6‐month follow‐up visits. Average age was 61.03 years (SD = 12.33, Range = 18–90 years) and the majority of the patients were White ( n  = 875, 89.0%). Three‐month responsiveness was calculated two ways, as between 80 and 100 days and as 90 days and beyond. Six‐month responsiveness was calculated as 170–190 days and as 180 days and beyond. All changes from baseline scores were significant at the 3‐,  >3‐, and >6‐month follow‐up ( p  < 0.05). All three measures showed large effect sizes, ranging from 0.80–1.20 at each time‐point. The standardized response mean was large for each measure and at each time‐point (Range = 1.06–1.53). This study demonstrated the responsiveness of the HOOS JR, KOOS JR, and the PROMIS PF in adult reconstruction patients. The PROMIS PF was consistently the most responsive instrument in this analysis. Clinical significance: The HOOS JR, KOOS JR, and PROMIS PF are useful clinical instruments for assessing treatment change and may be selected as relevant to the specific needs and conditions of the adult joint reconstruction patient population. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1178–1184, 2018.